Participatory Strategic Planning Model: Accelerating Digital Transformation and Competitiveness in Islamic Educational Institutions - Angga Setiawan; Akhmad Muaddin; Muchammad Eka Mahmud (Islamic Religious Education Master Program Universitas Islam Internasional Darullughah Wadda'wah, 2026)
Islamic educational institutions face dual pressures in the contemporary Society 5.0 era: preserving traditional religious values while rapidly responding to massive digital disruption. This study aims to formulate a conceptual model of participatory strategic planning to accelerate institutional competitiveness and navigate digital transformation effectively. Employing a qualitative approach with a Systematic Literature Review (SLR) design, this research systematically analyzes recent academic literature (2020–2026) regarding strategic management, participatory leadership, and educational technology in Islamic contexts. The findings reveal that centralized governance, often characterized by mono-leadership, significantly hinders institutional agility and stakeholder engagement. To overcome this managerial gridlock, the study proposes the Participatory Strategic Planning Model, which integrates three core pillars: the fundamental Islamic values of Shura and Amanah, an agile collective-delegative leadership structure, and the implementation of Islamic Digital Quality Management (IDQM). This model shifts strategic formulation into a data-driven, collaborative process utilizing SWOT analysis and PDCA cycles, effectively mitigating internal resistance toward digitalization. The study concludes that distributed authority and participatory governance are imperative for sustaining global competitiveness without compromising Islamic identity. Future empirical research across diverse educational typologies is strongly recommended to validate this conceptual framework.